Modernist Discourse and Qur'anic Interpretation in the Critical Thought of Mohammed Arkoun - Otaiwi, Faris Fadheel (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Contemporary Qur'anic interpretation often finds itself at the crossroads of tradition and modernity. Specific Background: One such tension is observable in the contrast between Mohamed Arkoun’s modernist hermeneutics and the traditional Shi‘i Imami exegetical framework. Knowledge Gap: While Arkoun's secular methodologies challenge established religious paradigms, limited research has critically examined their compatibility with metaphysically grounded Imami thought. Aims: This study critically analyzes Arkoun’s interpretive discourse through the lens of Imami hermeneutics, aiming to assess epistemological and methodological intersections. Results: It reveals fundamental divergences regarding the nature of the Qur’an—Arkoun treating it as a cultural construct subject to historical critique, while Imami thought preserves its divine, miraculous essence through a sacred interpretive tradition. Novelty: The paper juxtaposes Arkoun’s use of linguistics, anthropology, and sociology of knowledge with the theological underpinnings of Imami exegesis, offering an original comparative framework. Implications: The study concludes by evaluating the potential and limits of integrating modernist insights into traditional Islamic interpretation, thereby contributing to the broader discourse on reconciling critical methodologies with religious orthodoxy. Highlight: Contrasts Arkoun’s modernist lens with Imami theological principles. Highlights Qur'an’s dual role as sacred and cultural text. Assesses integration potential of critical secular tools in traditional hermeneutics. Keywords: Mohamed Arkoun, Modernist Discourse, Qur'anic Interpretation, Imami Exegesis, Islamic Thought